2023
DOI: 10.1139/cjfas-2022-0050
|View full text |Cite
|
Sign up to set email alerts
|

The estimated impact of changes to otolith field-sampling and ageing effort on stock assessment inputs, outputs, and catch advice

Abstract: Generating accurate data for stock assessments is resource-demanding, necessitating periodic evaluation of survey sampling designs and potential impacts on stock assessments. We developed a framework for bootstrapped resampling of survey age data and calculation of input sample sizes as a function of among-bootstrap variance in age compositions. Data from this bootstrap estimator were then used to evaluate the influence of alternative sampling rates and methods on uncertainty in estimates of the overfishing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To determine whether and when age composition ISS reaches an asymptote, simulation studies might be more appropriate rather than bootstrapping historical data, as variables such as life history or intrahaul correlation can be accounted for specifically (e.g., Hulson et al 2011;Xu et al 2020). The results of this study and Siskey et al (2023) suggest that the number of age samples necessary to maximize age composition information are likely beyond current management agency capacities. Our recommendation, therefore, is to attempt to retain, at a minimum, historical levels of sampling for age composition, as reductions in these sampling rates have downstream effects on assessment model uncertainty.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…To determine whether and when age composition ISS reaches an asymptote, simulation studies might be more appropriate rather than bootstrapping historical data, as variables such as life history or intrahaul correlation can be accounted for specifically (e.g., Hulson et al 2011;Xu et al 2020). The results of this study and Siskey et al (2023) suggest that the number of age samples necessary to maximize age composition information are likely beyond current management agency capacities. Our recommendation, therefore, is to attempt to retain, at a minimum, historical levels of sampling for age composition, as reductions in these sampling rates have downstream effects on assessment model uncertainty.…”
Section: Discussionmentioning
confidence: 97%
“…As we increased the subsampling rates for age composition, the age composition ISS continued to increase, indicating that a sample size producing diminishing returns had not been reached, unlike the asymptote observed for length composition ISS. In a similar study, Siskey et al (2023) evaluated the effect of increased age sampling beyond current sampling levels for a subset of stocks and found that the age composition ISS continued to increase, up to age sampling levels 67% greater than current rates. Siskey et al (2023) also found that, while holding the total age samples constant, improvements to age composition ISS were achieved by increasing sampling in more hauls even while decreasing the number of specimen age data collected in any given haul.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations